Basic physical pharmacy - Ma, Joseph K. H. (Jones & Bartlett Learning, 2013)
Basic Physical Pharmacy provides a thorough yet accessible overview of the principles of physical pharmacy and their application in drug formulation and administration. This definitive guide to physical pharmacy covers all types of pharmaceuticals, from traditional forms and dosages to nanotechnology-based novel dosage design.